2011
DOI: 10.1039/c1jm13898g
|View full text |Cite
|
Sign up to set email alerts
|

Origin of self-organisation in porous anodic alumina films derived from analogy with Rayleigh–Bénard convection cells

Abstract: Porous anodic aluminium oxide (PAOX) has different practical applications (e.g. filters with uniform pore sizes, adsorbers, porous templates for functional nanomaterials), but the formation mechanism is still poorly understood. Equal-sized hexagonally ordered pores are formed during anodic oxidation of aluminium in water solutions of some acids at certain concentrations and temperatures, and comparatively high electrode potentials. Today, a limited range of pore diameters and the degree of hexagonal ordering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
112
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(118 citation statements)
references
References 37 publications
4
112
2
Order By: Relevance
“…The results showed that although it is difficult to obtained self-ordered porous alumina film with an ideal hexagonal structure in squaric acid [25], the interpore distances in self-ordered AAO films prepared in other experimented acids are exceed 200 nm [24,26]. These discoveries of additional electrolytes and the corresponding theoretical model explaining the appearance of honeycomb structuregreatly expand the applicability of anodic porous alumina [27,28]. These efforts are successful in preparation of AAO films with big D int , while these values are only specific.…”
Section: Introductionmentioning
confidence: 60%
“…The results showed that although it is difficult to obtained self-ordered porous alumina film with an ideal hexagonal structure in squaric acid [25], the interpore distances in self-ordered AAO films prepared in other experimented acids are exceed 200 nm [24,26]. These discoveries of additional electrolytes and the corresponding theoretical model explaining the appearance of honeycomb structuregreatly expand the applicability of anodic porous alumina [27,28]. These efforts are successful in preparation of AAO films with big D int , while these values are only specific.…”
Section: Introductionmentioning
confidence: 60%
“…It is noted that our ADCA anodizing technique is effective at an unutilized voltage range of 87.5-95.0 V in previously described organic electrolytes. It is a well-known experimental fact that the nano-morphology, including pore diameter and cell size, strongly depends on the anodizing voltage 10,11,13,[28][29][30] . Therefore, ADCA anodizing is extremely useful for controlling and changing the nano-morphology of porous alumina for nanostructure fabrication.…”
Section: Methodsmentioning
confidence: 99%
“…The present study also reveals that chemical during anodizing of aluminium in aqueous acid electrolytes, i.e., 25 V in sulphuric acid [21], 40 V in oxalic acid [22] and 195 V in phosphoric acid [23]. In the present organic electrolytes, an optimized formation voltage appears to be present for the growth the ordered porous films, which should be between 30 and 50 V. The mechanism of self-ordering of pores in porous anodic films on metals is not yet understood and is the subject of further studies, although some models, including a stress-induced flow of film materials from a pore base to a pore wall, have recently been proposed [18,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%